ANALISIS PENGARUH IKLAN DAN KREDIBILITAS ENDORSER TERHADAP BRAND AWARENESS UNTUK MENINGKATKAN BRAND ATTITUDE PRODUK MINUMAN ISOTONIK MEREK MIZONE - Putranto, Budiawan Dwi; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2016)
The Problems in this study is less understood by consumers in the delivery of advertising, in addition to the celebrity used in advertising is less famous.This study aims to analyze the effects arising from the advertisement and endorser credibility on brand awareness and its impact on brand attitude of the product brand Mizone isotonic. The variables used in this study is an advertisement and endorser credibility as an independent variable, then the brand awareness as a latent variable and brand attitude as the dependent variable. The sample in this study a total of 120 respondents, partly students of the University of Muria Kudus S1 ever consume isotonic drink brands Mizone. The method used is purposive sampling by distributing questionnaires to the respondents. This study uses data analysis using analytical techniques Structural Equation Model (SEM), the analysis includes: a test measurement models, test confirmatory factor analysis, test CFA exogenous, test CFA endogenous, test the full model SEM, test data normality, test regression weight SEM , test reliability and test Sobel. Based on the results of Structural Equation Model (SEM) above shows that advertising (X1) and the credibility of the endorser (X2) significant effect on brand awareness (Y1) Mizone brand isotonic drinks products with regression coefficient of 0.555 and 0.372. While brand awareness (Y1) significantly influencethe brand attitude (Y2) Mizone brand isotonic drinks products with regression coefficient of 0.534.